Study of hesperetin effect on modulating transcription levels of MLH1 and MSH2 genes in SKBR3 breast cancer cell line - Naser Hameed Saleh; Ahmed Salim Kadhim Al-Khafaji; Esmaeil Babaei (Wolters Kluwer Medknow Publications, 2023)
Hesperetin (HSP), a flavonoid, has been validated to modify gene expression and function as an epigenetic agent to stop the development of breast carcinoma cells. HSP was investigated in this research to evaluate the expression of the MLH1 and MSH2 genes in cancerous breast cell lines (SKBR3) and healthy cell lines (MCF-11A) after exposure to different dosages (200, 400, and 600 μM/mL) of HSP. After 48 h of exposure, SKBR3's half-maximal inhibitory concentration was 289.6 μM/mL and MCF-10A's was 855.4 μM/mL. The research found that increasing HSP concentrations were closely correlated with an increase in MLH1 gene levels in the SKBR3 cell line, as shown by median and percentile values. HSP therapy caused the MLH1 gene expression to substantially vary in different groups, and in the SKBR3 cell line, MSH2 gene expressions were elevated in a dose-escalating manner. Moreover, HSP also raised the number of apoptotic cells, with the fraction of apoptotic cells escalating substantially at doses of 400 and 600 μM/mL. The outcomes suggested that HSP has the potential to be utilized as a therapeutic intervention for breast cancer, as it can induce apoptosis and reduce cell viability.